CHARACTERIZATION AND BIOLOGICAL STUDY OF 3-(4-BROMO-1-HYDROXYNAPHTHALEN-2-YL)-5-ARYL-1-SUBSTITUTED-PYRAZOLES - Sherkar, V. M.; Bhandarkar, S. E. (International Journal of Current Pharmaceutical Research, 2015)
4-Bromo-2-(1-substituted-5-aryl-pyrazolin-3yl)-naphthalen-1-ols were suspended in DMSO in 250 ml R. B. flask fitted with condenser and then crystal of Iodine was added to it. The reaction mixture was stirred and refluxed for 1 hour 30 Min. The contents were cooled and diluted with water. The product obtained was filtered and washed with 10% aqueous sodium thiosulphate and crystallized from ethanol acetic acid mixture to obtained 3-(4-bromo-1-hydroxynaphthalen-2-yl)-5-aryl-1-substituted-pyrazoles The synthesized compounds were characterized by elemental analysis, 1H NMR, IR Spectroscopy. All Newly synthesized compound were scanned for their antimicrobial activity and all newly synthesized compounds shows an excellent antimicrobial activities. Keywords: Synthesis, Characterization, IR Specra, NMR Spectra, Pyrazolines.